Konstruksi Sosial pada Pedagang Tradisional dalam Menghadapi Era Kompetisi Perdagangan Bebas - Komara, Beni Dwi; Prasetya, Agus (Universitas Muhammadiyah Gresik, 2019)
Article 33 of the 1945 Constitution aspires to the Indonesian economy being managed by the state with the aim of the prosperity of the Indonesian people. But the fact is that prosperity is only enjoyed by certain people and certain groups because the economy is only controlled by those who are only a small part of the Indonesian people. The growth of super markets, modern retail stores such as IndoMart, AlfaMart in all corners of the country, both villages and cities, has displaced traditional markets and caused traditional traders to go out of business. This is a violation of the constitution and must be stopped. Traditional traders are populist economic actors in the economic system, so the state must not commit arbitrariness, such as allowing competition, unhealthy competition between traditional traders and modern retail traders. This study aims: a). Knowing the need for social construction to traditional traders, b). what is the impact of the presence of modern retailers on traditional markets, c). the response of traditional traders to the mushrooming of IndoMart and AlfaMart, d). How should the local government protect Traditional market traders. This study uses a qualitative approach, with its social paradigm of social definition. Data retrieval through in-depth interviews, observation, documentation, while data analysis uses Interactive Miles and Hubermann Models. The results of the study show that it was necessary to do